The relationship between self-esteem and psychological well-being on stress among undergraduate students in Malaysia - Foo, Zyon Khang; Loh, Zhi Yuan; Yugambegai, Vijaya Kumaran (2022)
Stress is one of the most common phenomena among undergraduate students due to the increasing difficulty in tertiary education. Analyze the predictors for stress is going to help people to tackle with stress. Therefore, the current study is to investigate self-esteem and psychological well-being is a negative predictor toward stress among undergraduate students. This study used quantitative and cross-sectional research design. In this study, a total of 177 participants recruited by using convenience sampling method targeting undergraduate students from Universiti Tunku Abdul Rahman (UTAR), involving a total of 71 male students and 106 female students. Online questionnaire has been distributed across various social media platform such as Facebook, Whatsapp and Instagram. The participants’ age range must fall in between 18 to 24. The statistical analysis that has been used in this study is multiple linear regression on determining the predictors toward stress. The results in current study revealed that self-esteem negatively predicts stress while psychological well-being positively predicts stress among the undergraduate students. Thus, the hypothesis for self-esteem as negative predictor on stress is accepted but the hypothesis for psychological well-being as negative predictor on stress is rejected. In terms of practical implications, the findings may be useful for educationist, counselors and even parents as a reference to emphasize on what is important as a predictor toward stress. Future studies should emphasize on longitudinal study to examine the significant differences between two different time frames.